Structure Analysis and Efficiency Optimization of Two-stage 2K-H Closed Epicyclic Gear Trains - Wang Zhao; Wang Yong; Sheng Ruoyu; Huo Zhipu (Jixie chuandong)
A graphical analysis model is proposed to explore the possible structural patterns and efficiency. The research shows that the existence of cycle power is determined by the structure itself and has nothing to do with the characteristic parameter P. Six structural types with wide transmission ratios were proposed. In combination with the analysis model， the relationship between the transmission ratio and efficiency is discussed， and the transmission ratio range that there must be a cycle power in the condition of characteristic parameter P in [3，8] is obtained. Finally， the efficiency of a scheme is analyzed with this method， and the efficiency is improved by changing the tooth ratio.